Analysis of the Implementation of Total Productive Maintenance (TPM) at Madam Souvenir - Purba, Angel Theresia; Utami, Mulia; Lubis, Rahma Safitri; Gultom, Pesta (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This research aims to analyze the implementation of Total Productive Maintenance (TPM) at the Madam Souvenir Bakery in order to increase the effectiveness of production machines. The method used is Overall Equipment Effectiveness (OEE) measurement to assess machine performance based on three factors: availability, performance and quality. The OEE calculation results show a value of 72.2%, which is below the ideal standard of 85%. In-depth analysis identified